A paramedian forehead flap based on the axial artery and vein for nasal defects - Uslu, Asim (Annals of Medical Research, 2021)
None
Keywords: Paramedian Forehead Flap; Supratrochlear Artery; Supratrochlear Vein; Nasal Defect.